DETERMINANTS OF CHILD IMMUNIZATION AND MEASURMENT OF GENDER BIAS - Chatterjee, Poulami (European Scientific Journal, ESJ, 2014)
This paper attempts to analyse the role of some socio-economic and demographic variables on the likelihood of being fully immunised in Indian scenario . Six childhood vaccinations are being considered for the children of the age between one to two years in India. The data used in this paper are from the India Human Development Survey (IHDS), which was conducted in 2004-05 by the University of Maryland in collaboration with the National Council of Applied Economic Research, New Delhi between November 2004 and October 2005.The nationally representative data covers 1504 villages and 971 urban areas across33 states and union territories of India. The paper also tries to decompose the gender gap in full immunisation among children of age one to two years and tries to quantify the gender discrimination with regard to childhood immunisation.